Pengaruh Puisi Terhadap Kesehatan Emosional : Sebuah Tinjauan Pustaka: The Influence of Poetry on Emotional Health: A Literature Review - N.A, Septia Rizqi; Al Jamiliyati, Nasikhatul Ulla; Shafa, Sevi Ika Ariana; Yasmin, Aisyah; Maulida, Triska Amanda; Syafina, Velantika Puja Dwi Nara; Setyawati, Zahwa Alifia Aura Syfa (Yayasan Sagita Akademia Maju, 2025)
This study investigated the impact of poetry on mental health, focusing on how writing and reading poetry can help manage stress, depression and anxiety. Through a literary and experimental approach, poetry therapy has been shown to relieve emotional tension, increase self-esteem, and encourage deep introspection. Poetry as a creative therapeutic tool not only supports the emotional recovery process but also builds mental balance. Research findings show the potential of poetry as an effective therapy for improving emotional well-being in a variety of therapeutic and personal settings. This research investigates the impact of poetry on mental health, with the aim of understanding the mechanisms by which poetry functions as a therapeutic tool. Through a literary and experimental approach, poetry is proven to reduce stress, anxiety, and depression by encouraging self-expression and deep emotional introspection. Writing or reading poetry can help you articulate difficult emotions, support the emotional healing process, and improve your mental well-being. This research also shows that poetry therapy is effective in improving self-esteem and emotional stability in many people.